Customer profiling-based optimal load shaving solution using Evolutionary Programming technique: article - Zainudin, Muhd Ezzad Zaqwan (Faculty of Electrical Engineering, 2014)
This paper presents optimal load clipping and shifting using Evolutionary Programming (EP) technique. The problem formulation is based on the basic load clipping and load shifting knowledge. This process is conducted using the data provide by Malaysian Energy Commission (EC). The study considers several load categories namely the industrial, commercial and domestic loads. Results obtained from the study are beneficial for the basic understanding of load clipping and load shifting knowledge for the society. Evolutionary Programming technique is used to solve the optimization model of load shaving. MATLAB software is needed to put into practice the actual operation of the optimization process to provide the recommended decision, thus, avoiding system peak hour shortage problem in the future.